Employability Skills Model for Engineering Technology Students - Abdul Karim, Zatul Iradah; Maat, & Siti Mistima (Journal of Technical Education and Training, 2019)
The increasing unemployment rate among youth has affected Malaysian economic growth. This youth with tertiary education were the highest to be unemployed due to lack of experience, lack of labor market information and poor employability skills such as communication. Hence, TVET has become vital field in offering solution to the employability issue. This study aims to develop a prediction model in order to estimate the probability of obtaining high-level employability skills among engineering technology students in one of the technical institutes in Malaysia. A multinomial logistic regression analysis was implemented for this purpose. Through this prediction model, factors that contribute mostly to the high-level employability skills were identified. Using a random sampling technique, 204 engineering technology students from nine technical institutes were chosen to be the respondents of the study. A set of Students' Employability Skills Questionnaire of eleven items that include of Communication (3 items), Problem Solving (3 items), Teamwork (4 items), Planning and organizing (3 items), Creativity or Innovation (3 items), Working with others (3 items), Independent Study (3 items), Numeracy skills (2 items), ICT Skills (3 items), Self-Management (2 items) and Time management (3 items) was distributed. The collected data were analysed using SPSS version 22 in order to obtain multinomial logistic regression output. The result may be utilized by the technical institutes to predict the level of employability skills among engineering technology students for future employment in the job market. This implies a practical alternative for the similar issues among TVET graduates. The identification of lacking factors through the predictive model can be used in preparing the invention programs in order to reduce the unemployment rate among engineering technology graduates who become the job feeder in TVET area. Besides that, the contribution of this study is to fill the gap of the limitation study among TVET graduates as well.